"Thank you, woman, for being a woman": the feminine essence from a bioethical perspective - Pollack Orbegoso, Vanessa Marlith (2021)
Thinking and rethinking the feminine is the fruit of all time. Indeed, the centrality of the question of women and female genius is always at stake, always under discussion; therefore, it is a question of rediscovering the true meaning of femininity, as the central axis of human life, because it is. And, to understand the question of women, it is necessary to start from the anthropological, bioethical conception of corporeality, which is fundamental in the development of their own feminine spirit. What makes him who he is. The human person understood as a unit, bio psycho socio-spiritual; it is the one that is able to respond by itself, to the challenges and challenges of today's world, from its own reality of being who it is, from identity. And, from this recognition of identity, to be able to turn to action in the construction of a better world, of a better society, where the sacred value of all life and human dignity is respected.